PERANCANGAN VISUALISASI ANIMASI 2D INTERAKTIF SIKLUS PANJANG HIDROLOGI BERBASIS LAZARUS - Virginia, Stella (Universitas Bunda Mulia, 2023)
Technological advances have had a positive impact on various aspects, including education and understanding of natural phenomena. One natural phenomenon that is important to understand is the long cycle of the hydrosphere which involves changes in the phase of environmental water. The main goal of this design is to create a visualization that can clearly and comprehensively depict the long cycle of the hydrosphere. The design methods used include literature analysis, user interface design, hydrosphere cycle modeling, and implementation of interactive animation using Lazarus. The data and information needed to produce this animation were collected from trusted sources and verified by experts in the field of hydrology. Users can easily understand various aspects and processes of the hydrosphere cycle through interesting and informative animations. Lazarus, a Free Pascal-based software development environment, because it offers high flexibility and affordability in developing interactive 2D animation rendering applications. The result of this design is an interactive 2D animated visualization application that gives users an idea of how to explore the long cycle of the hydrosphere using interactive controls. Users can see the changes that occur at each stage and monitor the progress of the steps according to their wishes. It is hoped that this visualization will contribute to education and understanding of the hydrospheric cycle and will be a useful tool for teachers and students in interactive learning. Apart from that, the development of this application can be the basis for developing other visualizations related to natural phenomena.Keywords: 2D animated visualization, interactive, long cycle of the hydrosphere, Lazarus, Education